Surface acoustic wave spectroscopy in investigation of electrical properties of the near-surface region in GaAs crystals - PUSTELNY, T. (Archives of Acoustics, 1995)
The possibility of the appyling the surface acoustic wave of Rayleigh type to semiconductor investigations is described. The transverse acoustoelectric effect has been used to study the real surfaces of GaAs:Cd (111) and GaAs:Si (110) single crystals. The semiconductor surface in the layered structure: piezoelectric wave guide-semiconductor were performed. These investigations for different surface acoustic wave (SAW) frequencies were carried out. The values of the electric surface potentionall Φ_s the carrier density n_s as well as the effective life time τ_e of the minority carriers were obtained. The investigations were performed in a 50 ÷ 200 MHz frequence range. The dynamic values of these semiconductor surface parameters in a high frequency acoustic wave range were presented. The results have shown that the electrical and electron surface parameters may be various for different frequencies.